Universal Quasi-Level Parameter for the Characterization of Laser Operation - Christian Jirauschek (IEEE Photonics Journal, 2018)
A parameter is proposed which classifies the laser operating characteristics according to the quasi-level terminology, i.e., as intermediate behavior between that of an ideal two- and three-level or three- and four-level laser scheme. Since the quasi-level parameter is purely based on a generic rate equation description of the laser, no inherent assumptions about gain medium properties or the pumping process are required. The validity of the quasi-level parameter is verified for various prototypical laser schemes. As a specific example of a nonideal laser, the operating behavior of an experimental quantum cascade laser is classified, which constitutes a quite generic laser type since the active region properties can be custom-engineered by quantum design.